An Analysis of the Alignment of Archaeological Sites - Carlotto, Mark J. (Journal of Scientific Exploration, 2020)
There are hundreds, perhaps thousands of sites of archaeological importance throughout the world. In this study the alignments of over twohundred ancient sites were measured and analyzed. Sites are organized into eight geographic regions: South America, Mesoamerica, North America, Europe, the Middle East, Africa, Asia and the Pacific Ocean. Google Earth imagery and measurement tools were used to estimate the alignment of linear and rectilinear structures at these sites with respect to true (geographic) north. In considering standard celestial and geographic reasons for the alignments, many were found to be oriented to the cardinal directions, in the directions of solstices and other solar events, to lunar standstills, and certain stars. A number of sites in China and Thailand were likely aligned to magnetic north at the time of construction using a compass. Some sites appear to have been aligned to “sacred directions” that include Islamic qibla and Quechua ceques. Site alignment statistics reveal similarities and differences between geographical regions in terms of how sites within regions are aligned. Perhaps the most unexpected finding is that the alignment of about half of the sites could not be explained in terms of any of the reasons considered.